Impulsivity and non-suicidal self-injury in adolescents: a systematic review and meta-analysis of longitudinal studies - He, Xubin; Huang, Ping; Xu, XingHong; Yu, Qinyao; Huang, HongYan; Yang, Ping; Yang, Bo (Frontiers in Psychiatry, 2025)
BackgroundNon-suicidal self-injury (NSSI) is a prevalent and concerning behavior among adolescents, with impulsivity commonly considered an important risk factor. However, the strength of this relationship remains unclear. This systematic review and meta-analysis aim to assess the relationship between impulsivity and NSSI in adolescents, focusing on longitudinal studies.MethodsA comprehensive literature search was conducted across seven databases, with the search extending to February 1, 2025, to identify longitudinal studies on impulsivity and NSSI in adolescents. The effect sizes (odds ratio, OR) for each study were calculated, and a meta-analysis was performed to synthesize the results. Subgroup analyses were also conducted to examine whether the association between impulsivity and NSSI was influenced by factors such as region, age, impulsivity measurement tools, NSSI measurement tools, follow-up period, and study quality. A fixed-effect model was used to assess differences in effects across subgroups. All statistical analyses were performed using STATA 16.0 software.ResultsNine longitudinal studies involving 33,973 participants were included in the meta-analysis. A statistically significant positive correlation was found between impulsivity and NSSI in adolescents. The OR for NSSI was 1.09 (95% CI: 1.04, 1.16). Subgroup analyses revealed that Asian adolescents (OR = 1.18, 95% CI: 1.03, 1.36) and middle school students (OR = 1.11, 95% CI: 1.02, 1.20) were at a higher risk. These findings underscore the importance of targeting interventions towards these at-risk groups.ConclusionThis meta-analysis suggests that impulsivity is a significant predictor of adolescent NSSI. The findings highlight the importance of early identification of impulsive behaviors in high-risk adolescent groups, particularly in populations such as adolescents from Asia and middle school students.Systematic review registrationhttps://www.crd.york.ac.uk/prospero/display_record.php?ID=CRD42025641716, identifier CRD42025641716.